2020
DOI: 10.1177/0022242920959043
|View full text |Cite
|
Sign up to set email alerts
|

The Double-Edged Effects of E-Commerce Cart Retargeting: Does Retargeting Too Early Backfire?

Abstract: Consumers often abandon e-commerce carts, so companies are shifting their online advertising budgets to immediate e-commerce cart retargeting (ECR). They presume that early reminder ads, relative to late ones, generate more click-throughs and web revisits. The authors develop a conceptual framework of the double-edged effects of ECR ads and empirically support it with a multistudy, multisetting design. Study 1 involves two field experiments on over 40,500 customers who are randomized to either receive an ECR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Reporting the raw data (especially in a visual format) is an important step in explaining that the focal effects are directly observable in the real world. For example, in their field experiment testing the effects of early versus late reminders for abandoned e-carts, Li et al (2021) show the raw response rates to these reminders before embarking on a more sophisticated analysis. Of course, if an outcome of interest has multiple drivers, it may not be that easy to offer model-free evidence for a focal main or interaction effect.…”
Section: Offer Model-free Evidence Before Model Sophisticationmentioning
confidence: 99%
“…Reporting the raw data (especially in a visual format) is an important step in explaining that the focal effects are directly observable in the real world. For example, in their field experiment testing the effects of early versus late reminders for abandoned e-carts, Li et al (2021) show the raw response rates to these reminders before embarking on a more sophisticated analysis. Of course, if an outcome of interest has multiple drivers, it may not be that easy to offer model-free evidence for a focal main or interaction effect.…”
Section: Offer Model-free Evidence Before Model Sophisticationmentioning
confidence: 99%
“…For example, by building realistic shopping environments where respondents operate the online shopping process in their natural state, scholars can assess inhibitors of OSCA that arise at any time by monitoring respondents' clickstream data or face-to-face communication (Rubin et al, 2020 ). Using experimental scenarios also allows the observation of differential responses by segmenting based on time (Li et al, 2021 ), product categories (Zhao et al, 2021 ), and selling platforms (Jiang et al, 2021 ), which would tap into more valuable information. In addition, future researcher can used experimental design to compared the different generations (Generation X, Generation Y, and Generation Z) toward the perception of OSCA and how it could have different behavioral outcomes on OSCA and intention to visit brick-and-mortar retail stores.…”
Section: Discussionmentioning
confidence: 99%
“…From the review, we found that OSCA (e.g., Cho et al, 2006;Jiang et al, 2021) and purchase intention (Li et al, 2021;Zhao et al, 2021) are the most frequently studied outcomes. To clarify the drivers of OSCA research, this study examined it as a dependent variable reflecting the non-purchasing behavior of consumers.…”
Section: Arrangingmentioning
confidence: 99%
“…Both OSCA (Huang et al, 2018;Jiang et al, 2021) and purchase intention (Li et al, 2021;Zhao et al, 2021) were found to be the most frequently studied outcomes of the OSCA context.…”
Section: Outcome Variablesmentioning
confidence: 99%
See 1 more Smart Citation